An analysis of the water, energy, food and ecosystem (WEFE) nexus for Nepal - Pokharel, B. K.; Nepal, Santosh; Baral, S.; Gauchan, D.; Karki, S.; Pandey, V. P.; Vaidya, A.; Aryal, Anil; Baral, T.; Devkota, S.; Dhakal, M.; Gnawali, K.; et al. (International Water Management Institute (IWMI). CGIAR Initiative on NEXUS Gains, 2024)
This position paper advocates for the integration of the water, energy, food and ecosystem (WEFE) nexus approach into Nepal’s policy and planning processes. By doing so, it aspires to foster a development trajectory that is sustainable, inclusive, equitable and responsive to the needs of all citizens, particularly the vulnerable and marginalized groups, against a backdrop of accelerating climate change and resource interdependencies. The main contents of the paper are summarized below.